ANALISIS PENGARUH BIAYA AUDIT, PRAKTIK TATA KELOLA PERUSAHAAN, DAN STRUKTUR KEPEMILIKAN TERHADAP IPO UNDERPRICING - Oktiana Rustami; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2017)
This study aimed to examine the effect of audit fee, corporate governance structure, such as board size, audit committee, independent board of commissioner, and ownership structure  such  as  ownership  concentration,   institutional   ownership,  and  manajerial ownership  to  IPO  underpricing.  The  sampling  method  in  this  research  is  purposive sampling. The criteria used company is the company that has complete prospectus that include the amount of accountant public fee and the non-financial company. Based on the sampling criteria established during the years 2010-2015 was obtained by 83 companies. The analysis tool used is SPSS 21 with double linier regression analysis.The results show that fee audit and board size variables had negatively significant influence on IPO underpricing. Audit committee, independent board of commissioner, ownership concentration, institutional ownership, and manajerial ownership had no significant influence on IPO underpricing.